Aspek-Aspek Psikologi Dalam Psikologi Organisasi - Nasution, Imam Wahyudi; Wahyuni, Sri; S, Sukatin; Z, Zulqarnain (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Research in the field of organizational psychology also continues to grow, along with the need to understand the new generation of workers such as millennials and Gen Z who have different characteristics, values, and expectations from previous generations. Based on the description above, it can be concluded that psychological aspects in organizations are a vital part that cannot be ignored. Understanding and applying this science will help organizations manage human resources more effectively, efficiently, and ethically. Organizational psychology is an important field in understanding human behavior in the work environment. Aspects such as motivation, leadership, communication, group dynamics, work stress, and organizational culture greatly determine the effectiveness and well-being of the work. By applying the principles of organizational psychology, companies can increase productivity while creating a healthy work environment.